Exploring Factors Influencing Parent-Adolescent Communication on Sexual and Reproductive Health (SRH)—A Qualitative Study from Bengaluru, India - Likith R S (Journal of Psychosexual Health)
Background: Sexuality and reproductive health have remained a topic of taboo and disgust in India, owing to its deep-rooted cultural, traditional and religious practices. Lack of right sources of information and negligible communication about sexual and reproductive health (SRH) with trusted adults encourages adolescents to rely on unsafe sources, both online and offline, which could lead to detrimental consequences on their physical and mental health. Methods: This study utilizes a qualitative descriptive design to explore the factors influencing parent-adolescent communication on SRH. It focuses on mothers of adolescent children (10–19 years) from Urban Bengaluru. Data is collected through in-depth interviews of mothers and thematic analysis is performed on the data collected. Results: The qualitative analysis identified five core themes: Knowledge about SRH and gender-based needs, cultural and traditional influences, role of family, role of partner and inhibition of children. The perspectives of parents provided scope for what could be done to facilitate healthy and open communication. Conclusion: This study portrays the factors that hinder free communication between parents and adolescents about SRH. Suggestions for breaking the taboo pertaining to sexuality conversations and future studies have also been mentioned.